Leveraging teachable moments in cancer prevention by improving HPV vaccination in health professional students (HPS): A systematic review - Levy, Morgan S.; Finch, Lindsey; Lindsay, Kara A.; Jeudin, Patricia; Huang, Marilyn (Frontiers in Oncology, 2022)
Introduction Vaccination against HPV is safe and effective in cancer prevention, yet vaccination uptake remains low. Strong recommendation of HPV vaccination by healthcare providers increases immunization rates, but gaps in knowledge persist surrounding HPV and HPV vaccination amongst health professional students (HPS). It is critical to educate HPS in all professions to maximize vaccination opportunities and increase vaccine uptake. The objective of this study is to evaluate evidence on HPV knowledge, vaccine uptake, and educational interventions in HPS to identify specific deficits to improve education. Methods: A systematic literature search for articles on HPV vaccine uptake, knowledge, and educational interventions in HPS was performed in PubMed, Embase, Web of Science, CINAHL, and Scopus from January 1, 2006 – July 21, 2021. Included studies assessed HPS for HPV vaccine uptake, knowledge, counseling comfort, or educational interventions to increase HPV vaccine knowledge. Studies were screened for inclusion by 2 independent reviewers and evaluated for risk of bias. PRISMA guidelines for reporting were followed. Results: Twenty-one unique articles met inclusion criteria and were included in the analysis. Of the studies included, 20 included knowledge, 11 included vaccine uptake, 8 included interventions, and 12 included counseling comfort. The students in the studies included medical (n=14), dental (n=7), dental hygiene (n=6), nursing (n=3), physician assistant (n=2), public health (n=1), and pharmacy (n=1). Across studies, HPV vaccine series initiation ranged from 34.6-70.3%, with 28.3-58.3% up to date on vaccination. Most students knew that HPV causes cervical cancer (99%), but fewer knew that HPV causes head and neck cancer (40-47%) and oropharyngeal cancer (45%). Educational interventions included team-based approaches and lectures, and improved outcomes including vaccine knowledge, vaccination schedule, and cancer knowledge. Medical students with lower knowledge of HPV were more hesitant to recommend vaccination at baseline but were more likely to recommend vaccination after an education session. Discussion: Across HPS, inadequacies persist in HPV vaccine uptake, knowledge, and counseling comfort. It is critical to target vaccine uptake in this population and improve existing educational efforts to reduce preventable cancers. Institutions must prioritize HPV vaccine education to impact HPV related death.